2011
DOI: 10.1111/j.1651-2227.2011.02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of obesity from infancy to adolescence

Abstract: From 5 years of age, point estimates of body mass using only weight and height data are strongly associated with BMI at the age of 15. More data sources are needed to predict weight trajectories in younger children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Children who already have a high BMI at the age of 60–64 months are expected to have an earlier age at and a steeper slope of the adiposity rebound. In line with our observation, Angbratt et al 5 also reported that BMI at 5 years was closely associated with BMI at 15 years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Children who already have a high BMI at the age of 60–64 months are expected to have an earlier age at and a steeper slope of the adiposity rebound. In line with our observation, Angbratt et al 5 also reported that BMI at 5 years was closely associated with BMI at 15 years.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results are found in other studies. 5, 6 Several studies have also shown that birth weight and maternal smoking during pregnancy are associated with childhood obesity. 7, 8, 9, 10 Familial factors can explain up to 27% of the variance in a child's weight status.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also underline the importance of early obesity prevention [2,5,6,31,32]. Whitaker et al [31] showed that children with obesity under the age of three years are at low risk of obesity in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, obesity in preschool children correlates strongly with increased risk for obesity in adolescence [2]. This and many other well-documented associated health consequences of obesity [3] call for preventive interventions in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we did not find evidence to suggest that exposure to atole during the first 1000 d was associated with BMI latent class membership. Studies in high-income countries have shown an association between rapid growth before age 2 y and obesity risk (25)(26)(27); however, others found no increased risk when weight gain was appropriate for linear growth (28,29). A study of infant BMI trajectories in the Philippines found that accelerated infant BMI did not have longterm consequences on young-adult BMI (30).…”
Section: Discussionmentioning
confidence: 99%